Bacteria from the Amphibian Skin Inhibit the Growth of Phytopathogenic Fungi and Control Postharvest Rots - Gutiérrez Pavón, Adriana J. (2025)
Postharvest diseases caused by phytopathogenic fungi represent one of the main challenges in the agricultural industry, leading to significant losses in fruit production. Although chemical treatments have been widely used for the control of these pathogens, the emergence of resistant strains and concerns regarding food safety and environmental impact have driven the search for novel effective and eco-friendly alternatives, such as the use of biological control agents (BCAs). Previously, we demonstrated that bacteria isolated from frog skin inhibit the growth of the phytopathogenic fungus Botrytis cinerea. Based on these findings, in this study we aimed to investigate the biocontrol potential of three bacterial isolates obtained from the skin of the frog Craugastor fitzingeri. Dual culture assays showed that these bacteria strongly inhibited the mycelial growth of several postharvest fungal phytopathogens, including Penicillium digitatum, P. italicum, Alternaria alternata, Aspergillus niger, and Alternaria solani. This antagonistic activity was further confirmed through assays using bacterial filtrates (BFs) and volatile organic compounds (VOCs), effectively delaying or suppressing fungal development under in vitro conditions. Additionally, in vivo experiments on citrus fruits, tomato, and blueberry demonstrated that treatments with bacterial cell suspensions or BFs significantly reduced disease incidence caused by P. digitatum, A. alternata, and B. cinerea. However, no inhibitory effects were observed against Geotrichum citri-aurantii, Fusarium sp., Fusarium oxysporum, and Phytophthora capsici, suggesting a degree of specificity. Our findings highlight the potential of frog skin-associated bacteria as a novel source of BCAs for the sustainable management of postharvest diseases in fruits.